Analisis Kesulitan Guru Biologi dalam Mengembangkan Modul Ajar pada Kurikulum Merdeka di Sekolah Penggerak Kabupaten Temanggung - Darmawan, Ericka; Rachman, Fikri; Sukmawati, Ika (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The new policies included in the independent curriculum certainly have several different aspects. One of the differences here is in the teaching tools. In the independent curriculum, the Learning Implementation Plan (RPP) is referred to as a teaching module. Teachers can choose or even modify their own teaching modules that have been provided by the central government. Teachers need to develop teaching modules, but in reality there are still many teachers who experience difficulties in developing teaching modules. This research aims to determine the difficulties experienced by high school biology teachers in developing teaching modules. This study used qualitative research methods. The research subjects taken were the population of class X and XI Biology teachers at SMA Negeri 2 Temanggung, SMA Negeri 1 Candiroto, and SMA Negeri 1 Pringsurat. Data collection techniques used in research include observation, interviews and questionnaires. The research results show that the difficulty of Biology teachers in developing teaching modules is 45%. The level of difficulty is found in indicators of analysis and mapping of student needs, determining the dimensions of the Pancasila student profile, clarity of learning objectives, organizing teaching materials, determining learning models, determining and carrying out assessments, evaluating learning and following up on teaching modules, as well as difficulties in analyzing learning outcomes. will be reduced to a teaching module. The factors that make it difficult for Biology teachers to develop teaching modules are: 1) the number of students; 2) difficulty reading Learning Outcomes (CP); 3) the material is very short and unsystematic; 4) time constraints; 5) minimal reference for the implementation of the assessment; and 6) level of technological mastery. Thus, it can be concluded that the difficulties of high school biology teachers in developing teaching modules in the independent curriculum at Temanggung driving schools are in the